Effect of Glancing Angle Deposition to the Morphology of Calcium Phosphate Thin Coatings; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Prosolov K. A. Konstantin Alexandrovich; Belyavskaya O.; Rau J.; Sharkeev Yu. P. Yury Petrovich (Ion-Assisted Coating Deposition. Oral Presentation, 2019)
Заглавие с экрана